(untitled) (Revista Internacional de Folkcomunicação, 2021)
It is in the theory of folk communication, proposed by the author Luiz Beltrão in the 1960s, that the following article supports its theoretical and methodological aspects. For folk activism creates mechanisms of reading, identification, and actions in its own channels capable of overcoming post-truth, that is a deliberate distortion of reality. In this way, the objective is to highlight the role of folk activists in the democratic ruptures of Bolivian society, in a context where cyberspace seems to be an effective way of building new forms of social interaction, which together with citizen participation in the streets can produce actions and, effects in the reality. Civil resistance; Cyberativism; (Folk)media activism; Folk communicator.